Meu teto e meu pedaço de chão: uma avaliação do Minha Casa Minha Vida sob a ótica dos beneficiados - (:unkn) unknown (Universidade Federal do Amazonas, 2016)
This dissertation presents an evaluation of one of the largest housing programs implemented as public policy in Brazil, the Programa Minha Casa Minha Vida (PMCMV). The housing problem is currently the subject of great debate and controversy among the entities involved as governments, NGOs and civil society, which discuss the best solutions for existing housing deficit. In the city of Manaus (AM), the great migrations in search of better living conditions in the state capital and the lack of planning by families for decades, caused a swelling population without proper urban planning. As a result, the capital of Amazonas has the highest relative housing deficit in the country in 2010, which represents a significant part of the population living in an improvised way and often inappropriate, as the known 'stilts' or gullies slopes. This work therefore aims to evaluate the results of this new policy, specifically PMCMV in the city of Manaus (AM), in the perception of the beneficiaries. It is noteworthy that the investigation also included an analysis of the housing deficit before and after the implementation of the program. Therefore, a qualitative and quantitative research with 20 beneficiaries was performed and their results analyzed by the Collective Subject Discourse methodology (DSC), developed by Lefèvre and Lefèvre (2003). From the analysis of the speeches, it was found that the beneficiaries perceives as a result an improvement in their family’s quality of life, once there will be no more costs on property rental and they can make use of other financial achievements, raising the standard of family life. It is noted also an indirect benefit of MCMV: improvements on family’s self-esteem, for the social status that the ownership of a property represents in front of the society. Concepts such as solidity and safety, coming for their dwelling, are now more noticeable for the lowest income group. However, there were flaws inherent in the program implementation as poor service infrastructure provided by the government in the vicinity of housing, low quality property delivered and the lack of transparency in the process of access/selection of beneficiaries
Keywords: Políticas Públicas; Habitação; Programa Minha Casa Minha Vida; CIÊNCIAS SOCIAIS APLICADAS: ADMINISTRAÇÃO: CIÊNCIAS CONTÁBEIS